Comparison between Entecavir and Lamivudine as Hepatitis B Reactivation Prophylaxis in Cancer Patient with Chemotherapy - Nia Novianti Siregar; Rachmat Hamonangan; Dana Dharaniyadewi (The Indonesian Society for Digestive Endoscopy, 2015)
Aim: to compare between entecavir and lamivudine as hepatitis B reactivation prophylaxis in cancer patient with chemotherapyMethod: a literature searching in PubMed was done. At the beginning, 8 articles were found. Chosen article in this EBCR were those which compared lamivudine and entecavir directly to lymphoma patient in chemotherapy. Six articles were excluded. Besides PubMed, literature searching was done in Highwire, Cochrane, and Google Scholar too. In Google Scholar, one article that compared entecavir and lamivudine as hepatitis B prophylaxis in cancer patient was found in this study, there were also two multicenter retrospective study that will be appraised.Results: Hepatitis B virus (HBV) reactivation, HBV related hepatitis, and chemotherapy discontinuity as a consequence of Hepatitis B were found to be lower in entecavir groups. Entecavir was more effective in subjects with measured HBV deoxyribonucleic acid (DNA). In unmeasured HBV DNA groups, entecavir were as effective as lamivudine.Conclusion: entecavir were found to be more effective than lamivudine in patient with positive HBsAg or advanced stage of malignancy that were prepared for aggressive chemotherapy regiments. Since entecavir cost was unaffordable, lamivudine still a drug of choice in this situation.